2022
DOI: 10.1002/ccr3.5932
|View full text |Cite
|
Sign up to set email alerts
|

Dilemma of Tocilizumab therapy for a patient with critical COVID‐19 disease and neutropenia: Case report and review of the literature

Abstract: Infection following SARS‐Co V‐2 leading to COVID‐19 disease is associated with significant morbidity and mortality. The clinical entity, COVID‐19 cytokine storm syndrome (CSS) is a severe immunological manifestation of the disease associated with ominous consequences. Tocilizumab is interleukin‐6 inhibitors that has been shown to hamper the catastrophic outcomes of CCS including the need for mechanical ventilation as well as reduce mortality, but the usage is limited by warnings of reactivation of potential la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…The results of GO concentration analysis showed that cytokines and MHC class II protein complexes have important roles in the development of inflammation in scleritis disease, as suggested in several reports (26)(27)(28)(29). The top pathway enrichment analysis from the KEGG database was GVHD, which occurs in patients who have undergone allogeneic hematopoietic stem cell transplantation.…”
Section: Discussionsupporting
confidence: 56%
“…The results of GO concentration analysis showed that cytokines and MHC class II protein complexes have important roles in the development of inflammation in scleritis disease, as suggested in several reports (26)(27)(28)(29). The top pathway enrichment analysis from the KEGG database was GVHD, which occurs in patients who have undergone allogeneic hematopoietic stem cell transplantation.…”
Section: Discussionsupporting
confidence: 56%